A Different Pattern of Production and Scavenging of Reactive Oxygen Species in Halophytic Eutrema salsugineum (Thellungiella salsuginea) Plants in Comparison to Arabidopsis thaliana and Its Relation to Salt Stress Signaling - Pilarska, Maria; Wiciarz, Monika; Jajić, Ivan; Kozieradzka-Kiszkurno, Małgorzata; Dobrev, Petre; Vanková, Radomíra; Niewiadomska, Ewa (Frontiers in Plant Science, 2016)
Isolated thylakoids from halophytic Eutrema salsugineum (Thellungiella salsuginea) produces more H2O2 in comparison to glycophytic Arabidopsis thaliana. The first objective of this study was to verify whether this feature is relevant also to the intact chloroplasts and leaves. Enhanced H2O2 levels in chloroplasts and leaves of E. salsugineum were positively verified with several methods (electron microscopy, staining with Amplex Red and with diaminobenzidine). This effect was associated with a decreased ratio of O2•–/H2O2 in E. salsugineum in comparison to A. thaliana as detected by electron paramagnetic resonance method. As a next step, we tested how this specific ROS signature of halophytic species affects the antioxidant status and down-stream components of ROS signaling. Comparison of enzymatic antioxidants revealed a decreased activity of ascorbate peroxidase (APX), enhanced activity of glutathione peroxidase, and the presence of thylakoid-bound forms of iron superoxide dismutase (FeSOD) and APX in E. salsugineum. These cues were, however, independent from application of salt stress. The typical H2O2-dependent cellular responses, namely the levels of glucosinolates and stress-related hormones were determined. The total glucosinolate content in E. salsugineum water-treated leaves was higher than in A. thaliana and increased after salinity treatment. Treatment with salinity up-regulated all of tested stress hormones, their precursors and catabolites [abscisic acid (ABA), dihydrophaseic acid, phaseic acid, 1-aminocyclopropane-1-carboxylic acid, salicylic acid, jasmonic acid, cis-(+)-12-oxo-phytodienoic acid and jasmonoyl-L-isoleucine] in A. thaliana, whereas in E. salsugineum only a stimulation in ethylene synthesis and ABA catabolism was noted. Obtained results suggest that constitutively enhanced H2O2 generation in chloroplasts of E. salsugineum might be a crucial component of stress-prepardeness of this halophytic species. It shapes a very efficient antioxidant protection (in which glucosinolates might play a specific role) and a fine tuning of hormonal signaling to suppress the cell death program directed by jasmonate pathway.